Are Sex Differences in Preferences for Physical Attractiveness and Good Earning Capacity in Potential Mates Smaller in Countries With Greater Gender Equality?. (29th May 2019) - Zhang, Lingshan; Lee, Anthony J.; DeBruine, Lisa M.; Jones, Benedict C.
On average, women show stronger preferences for mates with good earning capacity than men do, while men show stronger preferences for physically attractive mates than women do. Studies reporting that sex differences in mate preferences are smaller in countries with greater gender equality have been interpreted as evidence that these sex differences in mate preferences are caused by the different roles society imposes on men and women. Here, we attempted to replicate previously reported links between sex differences in mate preferences and country-level measures of gender inequality in a sample of 3, 073 participants from 36 countries (data and code available athttps://osf.io/4sr5f/ ). Although women preferred mates with good earning capacity more than men did and men preferred physically attractive mates more than women did, we found little evidence that these sex differences were smaller in countries with greater gender equality. Although one analysis suggested that the sex difference in preferences for good earning capacity was smaller in countries with greater gender equality, this effect was not significant when controlling for Galton's problem or when correcting for multiple comparisons. Collectively, these results provide little support for the social roles account of sex differences in mate preferences.